Industrial training briefing: opportunities and challenges / Nurfaizah Kamarudin and Dr. Hajah Imilia Ibrahim - Kamarudin, Nurfaizah; Ibrahim, Imilia (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
As students, the most common way for them to acquire knowledge is through classroom instruction and occasionally through online techniques. Learning takes place not only in the classroom but also outside of it. On Friday, December 15, 2023, the faculty members gave the students a briefing on industrial training. This briefing aims to explain the information that is important to them before they begin their internship. Puan Nurfaizah Kamarudin presented the briefing to about one hundred students at 2:30 p.m., accompanied by Dr. Hajah Imilia Ibrahim. During the briefing, the students were attentive and focused on what was being said. Concerning the information that was exchanged, it was necessary to inquire about it with the selected organization. Regarding their internship, the students are responsible for finding a placement for themselves. The required information, such as the name and address of the organization, should be located close to their residence. It is also essential to provide the email address, telephone number, and the name of the person in charge. The students must identify two (2) suitable organizations that could provide them with industrial training. The first organization will be the primary and most important option when applying for an internship. In contrast, the second organization will serve as a backup plan if the first application is denied or there is no reaction from the organization.